Pengaruh Ekstrak Kulit Pisang dan Kulit Nanas terhadap Aktivitas Motorik dan Perilaku Tikus Wistar - Novia Novia; Fajar Nugraha; Siti Nani Nurbaeti; Inarah Fajriaty; Pratiwi Apridamayanti; Hadi Kurniawan; Liza Pratiwi (State University of Gorontalo, 2022)
Banana peel and pineapple peel are organic wastes that contain potassium, so it can potentially be developed into lozenges form as supportive antihypertensive therapy. Banana peel and pineapple peel as health supplement ingredients must meet safety requirements. The study of subchronic toxicity test was aimed to determine the toxic effect of repeated administration of a combination of banana peel and pineapple peel extract on motor activity and behavior of Wistar rats. The study was conducted by giving the test preparations repeatedly for 28 days in the control group, doses of 100 mg/KgBW, 400 mg/KgBW, 1000 mg/KgBW, control satellite, and satellite at 1000 mg/KgBW dose, as well as additional 14 days of observation in the satellite group to observe the reversibility effect. The test results showed that administering a combination of banana peel and pineapple peel extract showed normal observation on motor activity and behavior of Wistar rats. This study concludes that the combination of banana peel and pineapple peel did not give toxic effect on motor activity and behavior of Wistar rats.